Internal medicine and its physicians in the "resilient" search of its identity - Alfredo Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
This is a review in which the history of the internal medicine is focused on the basis of its relevance as specialty and, the way in which has been seen since the very moment of the emergence of the specialties from which they were derived. The advantages of the integral vision of the ill patient are manifested not only for the patient itself but also for the health institutions. It also analyzes the moral values an Internal Medicine specialist must have as well as the principles that may guide his/her formation.